Persistent Tachypnoea in Early Infancy: A Clinical Perspective - Samuel Menahem; Arvind Sehgal; Danielle F. Wurzel (MDPI AG, 2023)
Tachypnoea in the newborn is common. It may arise from the many causes of the respiratory distress syndrome such as hyaline membrane disease, transient tachypnoea of the newborn, meconium aspiration etc. Congenital heart disease rarely presents with early tachypnoea on day one or two, in contrast to the early presentation of cyanosis, unless there is "pump" (ventricular) failure such as may occur in a cardiomyopathy/myocarditis, or as a result of severe obstruction to either ventricle. Space-occupying lesions within the chest, for example from a diaphragmatic hernia or a congenital cystic adenomatoid malformation, may present with early tachypnoea, as can a metabolic cause resulting in acidosis. The aim of this paper, however, is to focus on infants where the tachypnoea persists or develops beyond the newborn period, at times with minimal signs but occasionally with serious underlying pathology. They include causes that may have originated in the newborn but then persist; for example, arising from pulmonary hypoplasia or polycythemia. Many congenital cardiac abnormalities, particularly those causing left sided obstructive lesions, or those due to an increasing left to right shunt from large communications between the systemic and pulmonary circulations, need be considered. Respiratory causes, for example arising from aspiration, primary ciliary dyskinesia, cystic fibrosis, or interstitial lung disease, may lead to ongoing tachypnoea. Infective causes such as bronchiolitis or infantile wheeze generally are readily recognisable. Finally, there are a few infants who present with persistent tachypnoea over the first few weeks/months of their life who remain well and have normal investigations with the tachypnoea gradually resolving. How should one approach infants with persistent tachypnoea?